Factors Associated with Late Presentation of HIV and Estimation of Antiretroviral Treatment Need according to CD4 Lymphocyte Count in a Resource-Limited Setting: Data from an HIV Cohort Study in India - Gerardo Alvarez-Uria; Manoranjan Midde; Raghavakalyan Pakam; Shanmugamari Kannan; Lakshminarayana Bachu; Praveen Kumar Naik (Interdisciplinary Perspectives on Infectious Diseases)
We describe the CD4 lymphocyte count at HIV presentation in an HIV cohort from a rural district of India. The majority of patients were diagnosed for their HIV-related symptoms, although a sizeable proportion of women were diagnosed because of antenatal screening or for having an HIV-positive partner. Patients diagnosed of HIV for antenatal screening or having an HIV-positive sexual partner had higher CD4 lymphocyte count than patients having tuberculosis or HIV-related symptoms. The proportion of patients diagnosed with CD4 count <200 and <350 cells/mm3 were 46% and 68.7%, respectively, and these figures did not change during the five years of the study. Factors associated with late presentations were male sex, older age, not having a permanent house, and, in women, lower education and being a widow or separated. With the implementation of 2010 WHO guidelines, the number of newly diagnosed patients who will require HIV treatment will increase 13.8%. If the CD4 count threshold for initiating HIV treatment is increased from 350 to 500 cells/mm3, the number of patients in need of treatment would increase 15.7%. Therefore, new strategies for avoiding HIV late presentation are urgently needed in developing countries.